Analysis of the Intensity of Electric Fields and Magnetic Fields in the Electrical Network Area Around the AC Blower - Hasan, Syarfidil Hamidil; Afita, Khofifah Afita; Mutiasari, Diva Ayu; Sudarti, Sudarti; Yushardi, Yushardi (International Journal of Education, Information Technology, and Others, 2025)
This study aims to investigate the magnetic field around an AC blower by measuring the magnetic field intensity, temperature, and humidity at distances ranging from 1 to 10 meters from the source. Each measurement point was repeated 10 times using a magnetic field meter, barometer, and altimeter to obtain accurate and comparable data. The measurement results indicate that magnetic field intensity decreases significantly as the distance from the AC blower increases, while temperature and humidity remain relatively constant throughout the measurement range. The data obtained was then analyzed to examine the relationship between the magnetic field and the surrounding environmental conditions. This study provides important insights into the characteristics of the magnetic field and environmental parameters around the AC blower, which can serve as a reference for environmental physics management as well as health and safety aspects.